Annual Plan 1976-77 - Planning Commission (Planning Commission, 1976)
The Annual Plan 1976-77 has been drawn up in the background of achievement of a degree of price stability and a significant improvement in the overall economic situation in 1975-76. The Plan also takes into account the new sense of discipline and dynamism brought about by the declaration of emergency and the launching of the New Economic Programme in the early part of the year 1975-76. All these elements are woven into a pattern of investment to meet the imperative need of the economy to accelerate considerably its rate of growth combined with stability.
Government of India Planning Commission
Government of India Planning Commission